PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PT. MATAHARI DEPARTEMENT STORE Tbk PERIODE 2013-2023 - Regi; Faisal (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the effect of the Current Ratio and Debt to Equity Ratio on the stock price of PT Matahari Department Store, Tbk. This research is quantitative with a descriptive approach. The sample used in this study consists of companies listed on the Indonesia Stock Exchange (IDX) based on the balance sheet and income statement reports of PT Matahari Department Store, Tbk for the 2013-2023 period. The results of the study indicate that, partially, the Current Ratio has a positive but not significant effect on stock prices, with a t-value (1.539) < t-table (2.262) and a significance level of 0.162 > 0.05. Meanwhile, the Debt to Equity Ratio has a negative but not significant effect on stock prices, with a t-value (0.594) < t-table (2.262) and a significance level of 0.569 > 0.05. Simultaneously, the Current Ratio and Debt to Equity Ratio variables also have no significant effect on stock prices, with an F-value (1.404) < F-table (4.46) and a significance level of 0.300 > 0.05.